Literary representations of capitalist dictatorship in transcultural adaptations of Brecht’s The Resistible Rise of Arturo Ui by Ajoka theatre in Pakistan - Kayani, Taimur; Ali Termizi, Arbaayah (Australian International Academic Centre, 2017)
Brecht’s ‘canonical’ literary work’s indigenization in Pakistan can offer a valuable transcultural adaptation study because it was performed through a radical theatre with a distinct dramaturgy and political philosophy in two different cultural contexts and historical frame of references. As the foremost representative of Brecht’s radical dramaturgy, philosophy and literary works in Pakistan since 1983, Ajoka theatre utilized these adaptations as socio-political spaces to challenge dominant discourses on the rise of dictatorship and capitalism in Pakistan. Prior studies explored the formal elements of these adaptations of The Resistible Rise of Arturo Ui(1942) : visual and aural and the intellectual content i.e. political dimension of this ‘social action theatre’ is still unexamined. This contextual reading attempts to fulfill this ‘gap’ by conducting a seminal contextual criticism on ‘literary representations’ of Pakistani pro-capitalist dictators in selected transcultural adaptations of Brecht’s work in light of new historicism and Hutcheon’s Theory of Adaptation. The article also explores how in the second phase Brecht’s social and political philosophy is reflected in Ajoka’s signature plays, Bala King (1997) and The Third Knock (1970).